Supercapacitive Properties of Micropore‐ and Mesopore‐Rich Activated Carbon in Ionic‐Liquid Electrolytes with Various Constituent Ions - Nguyen, Quoc Dat; Patra, Jagabandhu; Hsieh, Chien‐Te; Li, Jianlin; Dong, Quan‐Feng; Chang, Jeng‐Kuei (ChemSusChem, 2019)
Ionic‐liquid (IL) electrolytes, characterized by large potential windows, intrinsic ionic conductivity, low environmental hazard, and high safety, are used for micropore‐ and mesopore‐rich activated‐carbon (ACmicro and ACmeso) supercapacitors. IL electrolytes consisting of various cations [1‐ethyl‐3‐methylimidazolium (EMI+), N‐propyl‐N‐methylpyrrolidinium (PMP+), and N‐butyl‐N‐methylpyrrolidinium (BMP+)] and various anions [bis(trifluoromethylsulfonyl)imide (TFSI−), BF4−, and bis(fluorosulfonyl)imide (FSI−)] are investigated. The electrolyte conductivity, viscosity, and ion transport properties at the ACmicro and ACmeso electrodes are studied. In addition, the capacitance, rate capability, and cycling stability of the two types of AC electrodes are systematically examined and post‐mortem material analyses are conducted. The effects of IL composition on the charge–discharge capacitances of the ACmicro electrodes are more pronounced than those for the ACmeso electrodes. The FSI‐based IL electrolytes, for which electrochemical properties are cation dependent, are found to be promising. Incorporating EMI+ with FSI− results in a low electrolyte viscosity and a fast ion transport, giving rise to optimized electrode capacitance and rate capability. Replacing EMI+ with PMP+ increases the cell voltage (to 3.5 V) and maximum energy density (to 42 Wh kg−1) of the ACmicro cell at the cost of cycling stability. A puzzle of pores and ions: A suitable combination of activated carbon pore size and ionic‐liquid (IL) composition can achieve desirable electric double‐layer capacitor performance. A bis(fluorosulfonyl)imide (FSI)‐based IL is more promising than the bis(trifluoromethylsulfonyl)imide (TFSI)‐ and BF4‐based IL counterparts. Replacing 1‐ethyl‐3‐methylimidazolium with N‐propyl‐N‐methylpyrrolidinium increases the cell voltage to 3.5 V, improving the energy density of the supercapacitor.